Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I wanted to know how can I start to find the sum of the series:


I am having no clue.


share|cite|improve this question
Can you please cross check the numerator of the first term? – lab bhattacharjee Jul 26 '13 at 12:47
@lab, numerator is zero-factorial, seems right to me. – Gerry Myerson Jul 26 '13 at 12:59
@GerryMyerson, I thought the problem to be of type simple exponential type, so could not match the pattern:) – lab bhattacharjee Jul 26 '13 at 13:02
up vote 11 down vote accepted

Not nearly as impressive as the other answer, but elementary:

$$\begin{align} \frac{(4n)!}{(4n+4)!} &= \frac{1}{(4n+1)(4n+2)(4n+3)(4n+4)}\\ &= \left(\frac{1}{4n+1} - \frac{1}{4n+2}\right)\left(\frac{1}{4n+3} - \frac{1}{4n+4}\right)\\ &= \frac{1}{6} \frac{1}{4n+1} - \frac{1}{2}\frac{1}{4n+2} + \frac{1}{2}\frac{1}{4n+3} - \frac{1}{6}\frac{1}{4n+4}\\ &= \frac{1}{3}\left(\frac{1}{4n+1} - \frac{1}{4n+2} + \frac{1}{4n+3} - \frac{1}{4n+4}\right) - \frac{1}{6}\left(\frac{1}{4n+2} - \frac{1}{4n+4}\right) - \frac{1}{6} \left(\frac{1}{4n+1} - \frac{1}{4n+3}\right) \end{align}$$

It is well-known that

$$\sum_{n=1}^\infty \frac{(-1)^{n+1}}{n} = \log 2,$$

and the first parenthesis comprises four consecutive terms of that series, with no overlap, so from that we obtain $\frac{\log 2}{3}$. From the second parentheses, we can pull out a factor of $\frac12$ from both terms, then we obtain

$$\frac{1}{12} \left(\frac{1}{2n+1} - \frac{1}{2n+2}\right)$$

which comprises two consecutive terms of the $\log 2$ series, again without overlap, so together these two yield

$$\left(\frac{1}{3} - \frac{1}{12}\right)\log 2 = \frac{\log 2}{4}.$$

Another well-known series is Leibniz series

$$\frac{\pi}{4} = \sum_{k=0}^\infty \frac{(-1)^k}{2k+1}$$

and the last parenthesis comprises two consecutive terms of that, once again without overlap.

Since all parenthesised terms are dominated by $\frac{1}{n^2}$, we can split and rearrange to obtain

$$\begin{align} \sum_{n = 0}^\infty \frac{(4n)!}{(4n+4)!} &= \frac13 \sum_{n = 0}^\infty \left(\frac{1}{4n+1} - \frac{1}{4n+2} + \frac{1}{4n+3} - \frac{1}{4n+4}\right)\\ &\quad -\frac{1}{12}\sum_{n=0}^\infty \left(\frac{1}{2n+1} - \frac{1}{2n+2}\right)\\ &\quad - \frac16 \sum_{n=0}^\infty \left(\frac{1}{4n+1} - \frac{1}{4n+3}\right)\\ &= \frac{\log 2}{3} - \frac{\log 2}{12} - \frac16\frac{\pi}{4} = \frac{\log 2}{4} - \frac{\pi}{24}. \end{align}$$

share|cite|improve this answer
Mine was too similar. I've deleted it. – robjohn Jul 26 '13 at 17:34

$$ \begin{aligned} \sum_{n\geq 0}\frac{(4n)!}{(4n+4)!} & =\sum_{n\geq 0} \frac{\Gamma(4n+1)}{\Gamma(4n+5)} \\& =\sum_{n\geq 0}\frac{1}{6}\mathrm{B}(4n+1, \,4) \\& = \frac{1}{6}\sum_{n\geq 0}\int_{0}^{1}x^{4n}(1-x)^3\; dx\\& = \frac{1}{6}\int_{0}^{1} \frac{(1-x)^2}{(1+x^2)(1+x)} \; dx \\& = \frac{\ln 2}{4}-\frac{\pi}{24} \end{aligned}$$

share|cite|improve this answer
What does $\Gamma$ signify? :) – mikhailcazi Jul 26 '13 at 13:01
@mikhailcazi Gamma function. In the second line is the related Beta function – L. F. Jul 26 '13 at 13:03
(+1) Nice answer. – Mhenni Benghorbal Jul 26 '13 at 13:03
@MhenniBenghorbal Thank you! – L. F. Jul 26 '13 at 13:24
Forgive me for asking, but what college course would I take to learn how to answer this question in the same way? – Caleb Jares Jul 26 '13 at 17:49

$$\begin{align*} \sum_{n=0}^\infty\frac{(4n)!}{(4n+4)!} &=\sum_{n=0}^\infty\frac{1}{(4n+1)\times(4n+2)\times(4n+3)\times(4n+4)} \\& \end{align*}$$ And then decompose in simple element !

Use a fixed $N$ and evaluate the sum going from $0$ to $N$ by putting the 4 sums to the same start value and the same end value. Then everything will disapear.

share|cite|improve this answer

$$\begin{align*} \sum_{n=0}^\infty\frac{(4n)!}{(4n+4)!} &=\sum_{n=0}^\infty\frac{1}{(4n+1)\times(4n+2)\times(4n+3)\times(4n+4)} \\&=\frac{1}{8}\sum_{n=0}^\infty\frac{1}{32 n^4+80 n^3+70 n^2+25 n+3} \end{align*}$$

Now that we have replaced the nasty factorials with a nice, clean, rational function, we can use a more general procedure from here.

Also, if all you need to do is prove convergence, the comparison test is the simplest conclusive test.

If you want some additional stuff, here are the Wolfram Alpha queries for the equations: $\sum_{n=0}^\infty\frac{(4n)!}{(4n+4)!}$, $\frac{1}{8}\sum_{n=0}^\infty\frac{1}{32 n^4+80 n^3+70 n^2+25 n+3}$

share|cite|improve this answer
Why am I downvoted? – AJMansfield Nov 24 '13 at 21:53

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.